PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PRODUK OBRAL DENGAN IKLAN TANPA INFORMASI YANG JELAS (MENYESATKAN) - Muhammad Yasid; Nur Sakdiah (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2021)
The existence of products that are sold on sale from business actors to consumers can benefit both parties, (business actors and consumers). However, with the hidden conditions attached to the sale of products sold on sale, it is clearly very detrimental to consumers. To be able to attract more consumers' interest in buying sale products, business actors use advertising facilities. But unfortunately, most of these ads contain information that is not clear, thus violating the rights of consumers, which in the end, consumers also suffer losses. So the choice of the title of this article is "Legal Protection Against Consumers on Sale Products With Advertisements Without Clear (Misleading) Information."